The Relationship between Health Literacy, Preventive Health Literacy, and Cigarette Smoking Behavior of Undergraduates - Stalls, Juliann (East Carolina University, 2017)
Cigarette smoking is among the most detrimental of risky health behaviors and is related to multiple poor health outcomes including development of cancer. It is a complex behavior that is initiated and maintained through multiple factors: individual factors (e.g., psychological factors, stress), environmental factors (e.g., peer smoking behavior, accessibility), structural factors (local, state, and national policy) and sociodemographic factors (economic status and race/ethnicity). One individual factor, health literacy, has not been studied in relation to smoking behavior. In addition, a component of health literacy, preventive health literacy, has been mostly neglected by researchers. This involves one's knowledge of preventive health behaviors, risk perception of disease development, the belief in one's ability to make use of that knowledge and risk information to make good health behavior decisions (i.e., self-efficacy), and the ability to make preventive health actions (i.e., utilize preventive health care services and participate in positive health behaviors). Thus, the purpose of the current study was three-fold: 1) develop a better understanding of levels of health literacy and preventive health literacy, 2) determine if smoking behavior was associated with health literacy and preventive health literacy, and 3) examine the relationship between health literacy and preventive health literacy, among a sample of undergraduate students. The results indicated that health literacy and preventive health literacy as measured by health knowledge, risk perception, self-efficacy, and health action were high among the sample. However, only risk perception and health action significantly contributed to the prediction of smoking status. This finding suggests that smoking cessation programs may benefit from working to address engagement in positive health behaviors and improving risk perception, rather than health knowledge associated with smoking or self-efficacy to quit smoking. Furthermore, the results indicated that preventive health literacy did not offer a clear advantage over health literacy in the prediction of smoking status. These results were discussed and ideas for future clinical and research directions were provided.
Keywords: Smoking; Tobacco--Physiological effect; Undergraduates--Health and hygiene; Self-efficacy; Preventive health services--Utilization; Health literacy